All the world’s polar research data in one place: Fighting the 60% findability gap - Abu-Alam, Tamer (Septentrio Conference Series, 2019)
Data from the Polar Regions are of critical importance to modern research. Regardless of their disciplinary and institutional affiliations, researchers rely heavily on the comparison of existing data with new data sets to assess changes that are taking effect. In turn, knowledge based on as broad and comprehensive a selection of polar data sets as possible is used to inform politicians and decision makers. Although individual researchers and their institutions are aware of the importance of making collected data openly available through institutional websites, the infrastructures that are used for these purposes at many institutions, are often poorly interoperable, and therefore make valuable data difficult to find and reuse. In a recent survey of 113 major polar data providers, we found that an estimated 60% of the existing polar research data is unfindable through common search engines and can only be accessed through an institutional webpage. This findability gap limits the ability of researchers to establish robust models by which changes in the polar regions can be predicted. In this contribution, we present a new, free-to-use discovery service covering the global output of openly accessible polar research data and publications, with the purpose of rendering polar research more visible and retrievable to the research community as well as to the interested public, teachers and students and public services. The new service is currently under construction and will be hosted by UiT The Arctic University of Norway in close collaboration with the Norwegian Polar Institute.